PENGEMBANGAN MEDIA VIDEO ANIMASI EDUKASI UNTUK MENINGKATKAN HASIL BELAJAR PENJUMLAHAN SISWA KELAS II SD NEGERI 060861 PULO BRAYAN MEDAN - Dearni Inmaida Br Sinaga; Elvi Mailani; Albert Pauli Sirait; Fajar Sidik Siregar; Nur Hudayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop and examine the feasibility, practicality, and effectiveness of an educational animated video as a learning medium to improve second-grade students’ learning outcomes in addition at SD Negeri 060861 Pulo Brayan Medan. The study is motivated by the low learning outcomes in simple addition, caused by students’ difficulties in understanding concepts and the limited use of engaging and innovative learning media. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were second-grade students of SD Negeri 060861 Pulo Brayan Medan. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests. Data analysis was conducted to determine the validity, practicality, and effectiveness of the developed media. The results indicate that the educational animated video developed has a very high level of validity based on expert evaluations of both material and media aspects. Furthermore, the media is considered very practical based on positive responses from teachers and students during the learning process. The developed media is also proven to be effective in improving students’ learning outcomes, as indicated by an increase in scores before and after the use of the media. Therefore, the educational animated video is feasible to be used as an alternative learning medium to enhance mathematics learning outcomes in addition material at the elementary school level effectively and sustainably.